Oxygen Evolution Reaction: Enhanced Oxygen Evolution Reaction Activity of Nanoporous SnO2/Fe2O3/IrO2 Thin Film Composite Electrodes with Ultralow Noble Metal Loading (Adv. Mater. Interfaces 3/2019). Issue 3 (8th February 2019) - Haschke, Sandra; Zhuo, Ying; Schlicht, Stefanie; Barr, Maïssa K. S.; Kloth, Ricarda; Dufond, Maxime E.; Santinacci, Lionel; Bachmann, Julien
Abstract : Iron oxide (rust) is an attractive contender as a water oxidation anode material due to its stability and abundance. The limitations associated with its low catalytic activity and electrical conductivity are overcome by combining it with tin oxide and iridium oxide in a nanoporous geometry. More details can be found in article number1801432 by Sandra Haschke, Julien Bachmann, and co‐workers.